Determinación de parásitos gastrointestinales en carnívoros en el centro de México - Mino Botello, Daniel D.; Romero Callejas, Eva; Ramírez-Bravo, O. Eric; Aguilar Ubeda, Alejandra (Instituto de Ecología, A.C., 2016)
We report gastrointestinal parasites for three carnivore species in the region of Tehuacán, Central Mexico.